2013
DOI: 10.1152/ajpheart.00461.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dysfunction in young, mid-aged and aged mice with latent cytomegalovirus infections

Abstract: Gombos RB, Brown JC, Teefy J, Gibeault RL, Conn KL, Schang LM, Hemmings DG. Vascular dysfunction in young ec50, mid-aged and aged mice with latent cytomegalovirus infections. Am J Physiol Heart Circ Physiol 304: H183-H194, 2013. First published November 2, 2012; doi:10.1152/ajpheart.00461.2012.-Human cytomegalovirus (HCMV) is associated with vascular diseases in both immunosuppressed and immunocompetent individuals. CMV infections cycle between active and latent phases throughout life. We and others have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…These diseases have also been linked to HCMV infection. 20,21,51 In summary, our data indicate that ASCs are highly susceptible to HCMV infection and support its replication leading to release of infectious HCMV progeny. Furthermore, HCMV infection inhibits adipogenic differentiation and immunomodulatory function of ASCs.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…These diseases have also been linked to HCMV infection. 20,21,51 In summary, our data indicate that ASCs are highly susceptible to HCMV infection and support its replication leading to release of infectious HCMV progeny. Furthermore, HCMV infection inhibits adipogenic differentiation and immunomodulatory function of ASCs.…”
Section: Discussionmentioning
confidence: 58%
“…18 Long thought of as nonproblematic, HCMV latency is now being investigated for a possible role in chronic conditions including metabolic syndrome, cardiovascular disease, diabetes, cognitive impairment, and immunosenescence. [18][19][20][21] Recent studies show that HCMV infects progenitor cells of various types resulting in alterations in their phenotype and function. [22][23][24] The goal of this study was to determine if ASCs are susceptible and permissive for productive infection by HCMV, and if so, the consequences in terms of differentiation potential and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in experimental studies it was found that cytomegalovirus infection can induce severe endothelial dysfunction 50,51 and altered response to oxidized lipids in the subendothelium, 52 leading to atherosclerosis progression. However, the transition from experimental settings to clinical studies resulted in a contradiction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar setups are often used in studies on vascular physiology. 19,20 The experimental setup is schematically drawn in Figure 1.…”
Section: Methodsmentioning
confidence: 99%